Relationship between Serum Lipoprotein Ratios and Insulin Resistance in Polycystic Ovary Syndrome - Shou-Kui Xiang; Fei Hua; Ying Tang; Xiao-Hong Jiang; Qi Zhuang; Feng-Juan Qian (International Journal of Endocrinology, 2012)
Objective. To investigate the association between serum lipoprotein ratios and insulin resistance in women with polycystic ovarian syndrome (PCOS). Methods. 105 PCOS patients and 109 controls were randomly enrolled in the study. Serum levels of luteinizing hormone (LH), follicle-stimulating hormone (FSH), estradiol (E2), total testosterone (T), fasting glucose (FBG), fasting insulin (FINS), serum triglycerides (TG), total cholesterol (TC), high-density lipoprotein (HDL-C), and low-density lipoprotein (LDL-C) levels were checked, and then TG/HDL-C ratio, TC/HDL-C, ratio and LDL-C/HDL-C ratio were calculated. The homeostasis model assessment of insulin resistance (HOMA-IR) was used to calculate the insulin resistance. Results. All lipoprotein ratios were significantly higher in PCOS patients as compared to healthy controls (𝑃<0.05). TG/HDL-C ratio, TC/HDL-C ratio, and LDL-C/HDL-C ratio were significantly correlated with HOMA-IR (𝑃<0.05). The ROC curve demonstrated that TC/HDL-C ratio had higher sensitivity and specificity in diagnosing PCOS with insulin resistance. Conclusion. This study demonstrates that serum lipoprotein ratio significantly correlates with insulin resistance and can be used as the marker of insulin resistance in PCOS patients.